2015
DOI: 10.18632/genesandcancer.66
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs - a new horizon in molecular diagnosis of breast cancer

Abstract: BackgroundThe potential use of microRNAs (miRNAs) as ideal tumor markers has been the focus of recent research.ObjectiveOur hypothesis was that circulating miRNAs are differentially expressed in pretherapeutic sera of breast cancer patients compared to controls.Materials and MethodsUsing real-time quantitative polymerase chain reaction (qPCR) analysis, levels of 5 candidate miRNAs (miR10b, miR34a, miR155, miR195 and miR16) were quantified in sera of breast cancer patients and control individuals.ResultsLevels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 29 publications
(40 reference statements)
2
37
0
Order By: Relevance
“…A number of previous studies have indicated that miRNAs, being one of the main functional components of exosome cargo, may play a crucial role in cell-to-cell communication and eventually regulate the biological functions of recipient cells. It is known that miR-92a and miR-25-3p are up-regulated in cell lines with enhanced EMT, cell motility, and angiogenesis [ 25 , 26 , 27 , 28 , 29 , 30 ]. Since the miR-16-5p expression was stable and reproducible, it was chosen as an endogenous control to normalize the miRNA expression [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous studies have indicated that miRNAs, being one of the main functional components of exosome cargo, may play a crucial role in cell-to-cell communication and eventually regulate the biological functions of recipient cells. It is known that miR-92a and miR-25-3p are up-regulated in cell lines with enhanced EMT, cell motility, and angiogenesis [ 25 , 26 , 27 , 28 , 29 , 30 ]. Since the miR-16-5p expression was stable and reproducible, it was chosen as an endogenous control to normalize the miRNA expression [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Specific circulating miRNAs are useful markers for the diagnosis, therapy evaluation and prognosis of breast cancer. 35 , 36 , 37 miRNAs show different patterns of expression in the serum of breast cancer patients depending on their family subtypes or type of cancers. 38 For example, Das et al 39 reported that the level of miR-720 was relatively high in the serum of both primary and metastatic breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) represents the second most prevalent type of tumor with the highest mortality rate in the world among women. Annually, more than one million women are diagnosed with breast cancer and > 400,000 die from this disease [1]. The evolution of this neoplasm occurs when the cells break off and spread to other regions of the body [2].…”
Section: Introductionmentioning
confidence: 99%